Absorption of CO2 in aqueous blend of methyldiethanolamine and arginine. Issue 3 (22nd March 2020) - Talkhan, Ahmed Gomaa; Benamor, Abdelbaki; Nasser, Mustafa; El‐Naas, Muftah H.; El‐Tayeb, Sayed Ahmad; El‐Marsafy, Sahar
Abstract: The objective of this research is to study for the first time the effect of adding l ‐arginine (Arg) amino acid on the solubility of carbon dioxide in aqueous solution of N ‐methyldiethanolamine (MDEA). The study was carried out at different mixing ratios of MDEA and Arg at a total concentration of 2 moles per litre. The CO2 partial pressure varied from about 10 to 100 kPa, and the temperature varied from 293 K to 323 K. The experimental results showed improved solubility of CO2 with the addition of Arg at CO2 partial pressures below 20 kPa. However, for CO2 partial pressure of above 20 kPa, the addition of Arg caused a decrease in the solubility of CO2 . The obtained loading data were correlated using a semiempirical (SE) vapour liquid equilibrium (VLE) model with an average absolute deviation (AAD) less than 4.1% between the predicted and the experimental values. An estimation of the heat of CO2 absorption in the solution was obtained using an analytical expression for Δ H abs derived from the SE model and was found to be in the range of 29‐ to 40‐kJ/mole CO2 . From the finding of this work, it is anticipated that the studied novel blended solvent will effectively reduce CO2 capture costs as the CO2 content of most gas streams is less than 20% by volume, which is specifically true for natural gas and a large number of industrial flue gas streams.